The influence of nitrogen availability on anatomical and physiological responses of Populus alba × P. glandulosa to drought stress - Song, Junyu; Wang, Yang; Pan, Yuehan; Pang, Jiayin; Zhang, Xin; Fan, Junfeng; Zhang, Yi (BMC plant biology, 2019)
Drought and nitrogen (N) deficiency are two major limiting factors for forest productivity in many ecosystems. Elucidating the mechanisms underlying the influence of soil N availability on drought responses of tree species is crucial to improve tree growth under drought. The root proliferation under drought was enhanced by adequate N application. Vessel frequency in xylem increased upon drought, with more significant increase under adequate N conditions compared with that under low N conditions, possibly leading to increased hydraulic safety. Nitrogen application under drought increased indole acetic acid (IAA), which contributed to the adaptive changes of xylem. Nitrogen application increased leaf abscisic acid (ABA) concentration, therefore regulated stomata adjustment, and promoted intrinsic water use efficiency (WUE ). Moreover, N application promoted antioxidant defense in leaves by showing increased level of free proline and carotenoid, which improved drought tolerance and growth performance of poplars. Anatomical and physiological responses of Populus to drought were suppressed by N deficiency. Adequate N application promoted adaptive changes of root and xylem under drought and increased hydraulic safety. Nitrogen addition under drought also increased leaf ABA level which may regulate stomata adjustment and promote WUE . Moreover, nitrogen application improved antioxidant defense in leaves with increased levels of antioxidants. These positive regulations improved drought tolerance and growth performance of poplars.